Mapping Potential Environmental Impacts from Tourists Using Data from Social Media: A Case Study in the Westfjords of Iceland. - Hale, Brack W. (Environmental Management, 2018)
With tourism increasing in remote regions, it is important to be able to estimate potential environmental impacts from the tourists in order to plan and manage natural areas. This study combines measures of ecological sensitivity with data from publicly available geotagged photographs posted on the social media site Flickr to assess the vulnerability of the locations frequented by foreign tourists in the Westfjords region of Iceland between 2014 and 2016. The results suggest that tourists cluster primarily around six hotspots that represented some of the major known tourist destinations of the region. Although tourists generally frequented areas with lower ecological sensitivity and rarely went far beyond the main roads, one of the hotspots was in an area of higher ecological sensitivity. Further, tourists also appeared to have higher intensity stays when they entered areas of higher ecological sensitivity. Overall, these findings highlight the usefulness of combining data from social media in assessing potential environmental impacts of tourism. However, natural resource managers should be aware of limitations in the use of such data.